THE ROLE OF SELF-CONFIDENCE AND L2 IDENTITY CONSTRUCTION ON THE INDONESIAN STUDENTS’ SOCIAL INTERACTION IN NATURAL ENGLISH ENVIRONMENT - Rahmah, Nur Alfa (English Department of Faculty of Tarbiyah and Teacher Training, 2013)
Language learning involves a dynamic process of self confidence construction. A research by Jianwei Xu (2011) on the lived-experience of two Chinese advanced users of English in Australia shed a light on this. It also confirmed the nature of language as a complex social process that is closely bound to power relations and learner?s previously established L2 identity. However, it failed to notice how the self confidence and L2 identity play a role on maintaining smooth social interaction in natural English environment. In addition, the local and cultural boundary covered in the study was just coming from Chinese students, whom their mother tongues has quite different lexical form and structure from English. Indonesia, on the other side, has rather close lexical form and structure to English. Therefore, the research on the Indonesian learners? self-confidence in using English might show different result. This paper, then, is attempted to bring the discussion further and deeper to Indonesian users of English and how they undergo social interaction with their self-confidence and L2 identity in the English-speaking country. The researcher will interview three students from English department of State University of Malang who had experienced studying abroad to know how they construct their identity and confidence during their interaction with native-speakers and how does this contribute to the development of their English use.